Atomic-level nature of solid/liquid interface for energy conversion revealed by frequency modulation atomic force microscopy. (13th July 2021) - Minato, Taketoshi; Umeda, Kenichi; Kobayashi, Kei; Araki, Yuki; Konishi, Hiroaki; Ogumi, Zempachi; Abe, Takeshi; Onishi, Hiroshi; Yamada, Hirofumi
Abstract: Understanding and controlling the mechanism of energy conversion related to the development of a sustainable society not only make our lives more convenient but also make them more meaningful and enrichens us. The physical properties at the interface between solid and liquid (solid/liquid interface) play a significant role in energy conversion. The solid/liquid interface is buried and spatially limited, and thus clarifying the physical properties at the interface at the atomic scale is challenging. In this review, we describe our achievements by using frequency modulation atomic force microscopy for studying the geometric structure, molecule distribution, and viscosity at the solid/liquid interface at the atomic scale.